A critical role of Gas6/Axl signal in allergic airway responses during RSV vaccine‐enhanced disease. Issue 10 (15th August 2017) - Shibata, Takehiko; Ato, Manabu
Abstract : Respiratory syncytial virus (RSV) is a common virus that causes lower respiratory infections across a wide range of ages. A licensed RSV vaccine is not available because vaccination with formalin‐inactivated RSV (FI‐RSV) and the subsequent RSV infection cause not only insufficient induction of neutralizing antibodies but also severe allergic airway responses, termed FI‐RSV vaccine‐enhanced disease (FI‐RSV VED). However, the underlying mechanism has not been identified, although a Th2‐biased immune response is known to be a hallmark of this disease. Our previous studies have shown that growth arrest‐specific 6 (Gas6)/Axl signaling leads to Th2‐biased immune responses during fungus‐induced allergic airway inflammation. Here, we show that Gas6/Axl signaling also leads to FI‐RSV VED and partially identify the mechanism in mice. Inhibiting Gas6/Axl signaling using Gas6‐deficient mice, neutralizing antibodies, and a specific inhibitor of Axl attenuated allergic airway hyperresponsiveness, including airway inflammation, goblet cell hyperplasia, and Th2 cytokine production, in addition to increasing interferon‐γ levels and the production of RSV‐neutralizing IgG2a in FI‐RSV VED. Gas6 was produced in lymph nodes during immunization with FI‐RSV. Lymph node cells derived from immunized mice produced high levels of Gas6 and Th2 cytokines, but not IFN‐γ, after restimulation with RSV. Finally, we found that dendritic cells stimulated with RSV‐glycoprotein (G protein) produced Gas6 and that Axl signaling suppressed DC maturation and the induction of IL‐12 production by the toll‐like receptor 4 agonist RSV‐fusion protein. Taken together, these results indicate that RSV‐G protein‐induced Gas6/Axl signaling causes allergic airway responses during FI‐RSV VED.